Variation in Accessory Genes Within the Klebsiella oxytoca Species Complex Delineates Monophyletic Members and Simplifies Coherent Genotyping - Cosic, Amar; Leitner, Eva; Petternel, Christian; Galler, Herbert; Reinthaler, Franz F.; Herzog-Obereder, Kathrin A.; Tatscher, Elisabeth; Raffl, Sandra; Feierl, Gebhard; Högenauer, Christoph; Zechner, Ellen L.; Kienesberger, Sabine (Frontiers in Microbiology, 2021)
Members of the Klebsiella oxytoca species complex (KoSC) are emerging human pathogens causing infections of increasing significance especially in healthcare settings. KoSC strains are affiliated with distinct phylogroups based on genetic variation at the beta-lactamase gene (blaOXY) and it has been proposed that each major phylogroup represents a unique species. However, since the typing methods applied in clinical settings cannot differentiate every species within the complex, existing clinical, epidemiological and DNA sequence data is frequently misclassified. Here we systematically examined the phylogenetic relationship of KoSC strains to evaluate robustness of existing typing methods and to provide a simple typing strategy for KoSC members that cannot be differentiated biochemically. Initial analysis of a collection of K. oxytoca, K. michiganensis, K. pasteurii and K. grimontii strains of environmental origin showed robust correlation of core phylogeny and blaOXY grouping. Moreover, we identified species-specific accessory gene loci for these strains. Extension of species correlation using database entries initially failed. However, assessment of average nucleotide identities (ANI) and phylogenetic validations showed that nearly one third of isolates in public databases have been misidentified. Reclassification resulted in a robust reference strain set for reliable species identification of new isolates or for retyping of strains previously analyzed by multi-locus sequence typing (MLST). Finally, we show convergence of ANI, core gene phylogeny, and accessory gene content for available KoSC genomes. We conclude that also the monophyletic members K. oxytoca, K. michiganensis, K. pasteurii and K. grimontii can be simply differentiated by a PCR strategy targeting blaOXY and accessory genes defined here.